The limited oncogenic potential of unilocular adnexal cysts: A systematic review and meta-analysis. (June 2018) - Parazzini, Fabio; Frattaruolo, Maria Pina; Chiaffarino, Francesca; Dridi, Dhouha; Roncella, Elena; Vercellini, Paolo
Abstract: The reported frequency of malignant diseases in unilocular cysts varies in different studies, giving conflicting results. To quantify the risk of malignancies among echoic and anechoic unilocular adnexal cysts, in premenopausal and postmenopausal women, we performed a PubMed/MEDLINE search of papers published in English evaluating the histopathological diagnoses of removed ovarian cysts diagnosed as simple unilocular cysts at pre-operative ultrasound examination. From 34 selected publications, we extracted data on ovarian malignancy in the total series, and separately for premenopausal and postmenopausal women, and women with cysts < 5 cm and  ≥5 cm in diameter. Of the 2177 surgically removed lesions classified as unilocular cysts on pre-operative ultrasound, 24 (1.1%; 95% CI: 0.74–1.66) were malignant (among these 12 had borderline malignancy: 0.6%). The rates were lower for premenopausal women (6/987, 0.6%) than postmenopausal ones (12/372, 3.2%). Of the 2290 surgically removed lesions classified as anechoic unilocular cysts on ultrasound, 20 (0.9%; 95% CI: 0.57–1.35) were malignant (among these 8 had borderline malignancy: 0.3%). The rates were lower for premenopausal women (3/907, 0.3%) than postmenopausal ones (13/681, 1.9%) (Pearson chi-square P  = 0.002). When we performed meta-analysis selecting studies including only anechoic unilocular cysts published after 2000 and with 100 or more patients, the estimate was 0.5 (95% CI 0.1–1.2) with no heterogeneity (heterogeneity chi-square P  = 0.175). The oncogenic risk of unilocular adnexal cysts is low, suggesting that the final choice about surgical treatment of these cysts should be based on the combination of each patient's overall risk profile as well as personal priorities.